2022
DOI: 10.3390/cancers14143470
|View full text |Cite
|
Sign up to set email alerts
|

Overall Survival Improvement in Patients with Epidermal Growth Factor Receptor-Mutated Non-Small Cell Lung Cancer and Bone Metastasis Treated with Denosumab

Abstract: The impact of an initial skeletal-related event (SRE) and denosumab adjuvant treatment on the survival outcome of epidermal growth factor receptor (EGFR)-mutated non-small cell lung cancer (NSCLC) patients with bone metastasis remains unclear. This retrospective study included 400 metastatic EGFR-mutated NSCLC patients. Among 190 bone metastasis patients, 61 had initial SREs and 73 received denosumab. We analyzed patient characteristics, SRE-free survival (SRE-FS), and overall survival (OS). In metastatic EGFR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…In a retrospective study of 190 NSCLC patients with BoM, combining denosumab with first-or second-generation EGFR-TKI was associated with improved OS (26.6 vs. 20.1 months; p = 0.015). 20 However, another real-world study reported that denosumab had no significant prognostic effects in lung adenocarcinoma patients with BoM treated with first-line EGFR-TKIs. 21 In our study, combining EGFR-TKI with denosumab showed a nonsignificant trend toward improving the OS of EGFRmutated NSCLC patients with BoM.…”
Section: (A) (B) (C)mentioning
confidence: 99%
See 4 more Smart Citations
“…In a retrospective study of 190 NSCLC patients with BoM, combining denosumab with first-or second-generation EGFR-TKI was associated with improved OS (26.6 vs. 20.1 months; p = 0.015). 20 However, another real-world study reported that denosumab had no significant prognostic effects in lung adenocarcinoma patients with BoM treated with first-line EGFR-TKIs. 21 In our study, combining EGFR-TKI with denosumab showed a nonsignificant trend toward improving the OS of EGFRmutated NSCLC patients with BoM.…”
Section: (A) (B) (C)mentioning
confidence: 99%
“…Third, our study does not report on SREs, which previous studies have identified as a poor prognostic factor. 20,21 Fourth, we used different dosages of bevacizumab (7.5 mg/kg every 3 weeks) and intravenous ramucirumab (5-10 mg/kg every 3 weeks) compared to prior trials, 22,23 due to these drugs not being covered for lung cancer treatment under Taiwan's National Health Insurance, leading to the use of reduced dosages. Previous research showed that combining chemotherapy with 7.5 mg/kg of bevacizumab was as effective as using 15 mg/kg.…”
Section: (A) (B) (C)mentioning
confidence: 99%
See 3 more Smart Citations